Yāminī Rāẏa : tm̐āra śilpacintā o śilpakarma bishaẏe kaẏekaṭi dika - Dey, Bishnu (Āśā Prakāśanī, 1977)
On the artistic genius of the Bengali painter Jamini Roy, 1887-1972; study includes letters of Roy to Bishnu Dey.